Follow-up of a postoperative pregnant woman with low-grade oligodendroglioma - Rampazzio, Elisangela Maria Nicolete; Lopez, Fernando Kawaminami; Angelo, Maria Clara Berto de; Pereira, Lucas Brandão; Novaes, Maria Clara França Gregolini; Gonçalves, Giovana Gasparoto; Silva, Letícia Moelas da; Coluna, João Marcelo (Seven Editora, 2024)
Central Nervous System (CNS) neoplasms do not usually comprise the epidemiological profile of women of childbearing age, affecting more men in a ratio of 2:1 in the fourth or fifth decade of life. There is no consensus in the literature on risk factors and related family history in relation to the individual’s gender, however, some studies suggest a neuroprotection deficit due to the absence of estrogen, which, in women, could be related to the indiscriminate use of hormonal contraceptives alone, such as capsules and/or progesterone injections, since estrogen has been proven to play an important role in the deployment of central nervous system cells. The symptomatology secondary to grade II oligodendrogliomas usually refers to epilepsy and headache, which are accompanied by little improvement to medications. Resolution, in this case, consists of surgical tumor resection and usually has a good prognosis when diagnosed early. In the cases of young women diagnosed with oligodendrogliomas and undergoing a well-disciplined clinical-surgical therapy, family planning is possible and of great importance. They usually have uneventful gestational development and a smooth delivery, as long as they are assisted by a multidisciplinary team. To this end, physicians must take advantage of scientific evidence that supports the use of medications and the choice of imaging method to monitor the evolution of the case. In cases of malignant CNS neoplasia, local chemotherapy may be an option. Surgical reapproach should be considered with great caution and the decision should always prioritize the health of the mother over that of the developing fetus. DOI:https://doi.org/10.56238/sevened2024.001-024